1995
DOI: 10.1007/bf00301771
|View full text |Cite
|
Sign up to set email alerts
|

Antiperinuclear factor: a useful test for the diagnosis of rheumatoid arthritis

Abstract: The objective of this study was to determine: (1) the diagnostic value of antiperinuclear factor (APF), (2) the types of immunoglobulins involved in the reaction and (3) the presence of the antibody in paired samples of serum and synovial fluid (SF). We studied 408 serum samples from the following: healthy controls (n = 68), patients with rheumatoid arthritis RA; n = 160, 106 RF-positive and 54 RF-negative and patients with other rheumatic diseases (n = 180). We examined paired serum and SF samples in 27 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…16 17 However, we used a cut off titre of 1:40 because in an earlier study5 we found that a cut off of 1:10 had relatively poor specificity for RA. In several countries, the frequency of AKA18 or anti-RA 33 antibodies1 is considerably lower than in most of Europe 4 5…”
Section: Discussionmentioning
confidence: 99%
“…16 17 However, we used a cut off titre of 1:40 because in an earlier study5 we found that a cut off of 1:10 had relatively poor specificity for RA. In several countries, the frequency of AKA18 or anti-RA 33 antibodies1 is considerably lower than in most of Europe 4 5…”
Section: Discussionmentioning
confidence: 99%
“…Generally, IgG class of AB is important [5,6]. Due to sensitivity of (36 -87%) [7][8][9][10][11][12] and high specificity of (73-100%) [10,11] is a valuable serological tool for the diagnosis of the disease [7,10] and a useful serological marker to differentiate this disease from the other inflammatory rheumatoid diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, one clinical use of anti‐CCP antibody testing could be in combination with RF testing in order to improve the sensitivity of the serologic diagnosis of RA. Additionally, the anti‐CCP autoantibody system has been associated with progression to erosive RA and a more severe disease course (26, 28, 29). Therefore, this autoantibody system may contribute to clinical decision‐making regarding therapy for RA.…”
mentioning
confidence: 99%